2019 15th International Wireless Communications &Amp; Mobile Computing Conference (IWCMC) 2019
DOI: 10.1109/iwcmc.2019.8766466
|View full text |Cite
|
Sign up to set email alerts
|

Fast CNN-Based Object Tracking Using Localization Layers and Deep Features Interpolation

Abstract: Object trackers based on Convolution Neural Network (CNN) have achieved state-of-the-art performance on recent tracking benchmarks, while they suffer from slow computational speed. The high computational load arises from the extraction of the feature maps of the candidate and training patches in every video frame. The candidate and training patches are typically placed randomly around the previous target location and the estimated target location respectively. In this paper, we propose novel schemes to speedup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Accordingly, the training patches are not forwarded through the convolutional layers, and hence, a significant reduction in the processing time is achieved. As reported in [3], a comparable performance with the baseline tracker is achieved for all the tracking challenges, while obtaining a speed improvement of 8.8x on the same CPU. Fig.…”
Section: Overview Of Ilnet Trackersupporting
confidence: 60%
See 3 more Smart Citations
“…Accordingly, the training patches are not forwarded through the convolutional layers, and hence, a significant reduction in the processing time is achieved. As reported in [3], a comparable performance with the baseline tracker is achieved for all the tracking challenges, while obtaining a speed improvement of 8.8x on the same CPU. Fig.…”
Section: Overview Of Ilnet Trackersupporting
confidence: 60%
“…The main idea of ILNET [3], however, is to reduce the number of the convolutional computations in the network, and hence, achieve a processing speed-up factor. The whole Region of Interest (ROI) is forwarded to the network instead of small random patches and a 15x15x512 feature map is obtained.…”
Section: Overview Of Ilnet Trackermentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the VOT methods based on deep learning specifically Convolutional Neural Networks (CNNs) (Girshick et al, 2014, Girshick, 2015, Ren et al, 2015, Lin et al, 2017 have shown promising performances in MOT scenarios (Wojke et al, 2017, Bewley et al, 2016. However, most of these methods suffer from high computational costs and slow processing, especially extracting features from each candidate object locations in every frame (El-Shafie et al, 2019). The complexity increases exponentially by increasing the number of objects.…”
Section: Introductionmentioning
confidence: 99%